Eksistensi dan Gerakan Dakwah Tarekat á¹¢iddÃ®qÃ®yah di Tengah Masyarakat Urban Surabaya - Shodiq, Muhammad (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
The article attempts to analyze the existence of Tarekat ?iddîqîyah community in Surabaya focusing on its struggle and development process from minority to be relatively a well-established Sufi order, which has many branches in many areas in Indonesia. In Surabaya, Tarekat ?iddîqîyah has established four branches of caliphate, which locate in Tandes, Perumahan Pondok Candra, Karangrejo Wonokromo, and Manukan Kulon. It has also founded a branch that focuses on education in Nglampis Ngasem. The author finds that Tarekat ?iddîqîyah promulgated its teachings in Surabaya by spreading information manually, from person to person and coordination among its followers, and formation of spiritual organizations, namely YPS and Orshid. The advent of ?iddîqîyah to Surabaya has been done through infiltration, identification, coordination, and mobilization. In addition, the author finds that there have been various motives of Surabaya people in adhering ?iddîqîyah, such as improving their religious knowledge, joining a socio-spiritual community/fraternity, having a lifeline in the form of dhikr and wirid, and having prayer to prevent themselves from committing immoral deeds (tolak balak). The followers of ?iddîqîyah also claim that the tarekat has been able to fulfill their spiritual needs. Social interaction of ?iddîqîyah?s members amongst Surabaya people in general runs peacefully and harmoniously for they can assimilate and adapt to the local culture.